Manajemen Konflik dalam Penertiban Pedagang Kaki Lima Di Kawasan Pantai Padang - Viska Anggraini; Syamsir Syamsir; Stellina Shakira; Tsurayya Annisa; Adelya Jesika Eriza; Tasya Putri Ayunda (Dinasti Research, 2023)
This research aims to determine conflict management in controlling street vendors (PKL) in Padang Beach area. This research was conducted using qualitative methods with the data source derived from verbal interviews with street vendors who were directly affected by efforts to implement the Padang City Regional Regulations, Law Number 3 of 2014 concerning the Arrangement and Empowerment of Street Vendors, and observation. The indicators contained in this research are the factors that cause conflict, the impact of conflict, and conflict resolution. Based on the results of this research, it can be concluded that conflict resolution between street vendors and the government has not run optimally. This conflict also has a positive impact on the city's spatial management, but it has a negative impact on street vendors due to reduced income generated